Penguatan Pendidikan Karakter Remaja melalui Sinergi Manajemen Keluarga, Sekolah, dan Lingkungan - Junaidi, Junaidi; Apriliiaty, Fitriana; Yuza, Geby Fadilla; Arisandi, Diki (EL-EMIR INSTITUTE, 2025)
Character education for adolescents requires collaboration between family, school, and the surrounding community. However, many community service programs still emphasize partial interventions and rarely integrate family management, school management, and environmental culture in a structured manner. This community service program aimed to strengthen adolescent character education through the synergy of family management, school management, and environmental culture. The activity involved 35 participants consisting of parents and community representatives. Evaluation was conducted using a pretest–posttest approach to measure changes in participants’ understanding, including aspects of communication patterns, role modeling, environmental influence, shared responsibility, and self-efficacy in guiding adolescents. The results showed an increase in the average score from 70.5 in the pretest to 85.5 in the posttest, representing a 21.3% improvement. The findings indicate that strengthening synergy among family, school, and community environments can enhance participants’ awareness and understanding of collaborative responsibility in shaping adolescent character. This program contributes practically by offering an integrative model of character education reinforcement at the community level.